An Empirical Analysis of Influencing Factors of Government Decision-Making on Public Crisis - Tuo Wang; Shiqing Chen; Chuleerat Kongruang (Ital Publication, 2024)
As the times and the world are changing in an unprecedented way, public security issues have become increasingly linked, transnational, and diverse, causing huge impacts on the global economy and society, as well as posing great challenges to the government in dealing with public crisis decision-making. This study aims to determine the factors affecting the government's crisis decision-making and analyze the interrelationship among the factors affecting the government's crisis decision-making and the performance of its crisis decision-making. The questionnaire was developed and used to collect data from 400 samples of various groups, including government department personnel, scientific research institute practitioners, university lecturers, the public, and university students, both online and face-to-face. The structural equation model (SEM) is used to evaluate the structural relationships of the relevant variables, including the crisis decision-making body, crisis decision-making procedure, crisis decision-making performance, the decision environment, and value identification. It is found that the diversified decision-making subject and decision-making environment have a positive and significant impact on the public crisis decision-making process, value identification, and decision-making performance, respectively. This study has contributed to the following issues. Firstly, it developed new measurement tools and indicators for better evaluating the quality and effect of public crisis decision-making and exploring the influence of different factors on the crisis decision-making of the government. Secondly, it employed cross-industry and cross-cultural comparative research to find commonalities and differences and provide targeted recommendations. Doi: 10.28991/ESJ-2024-08-02-03 Full Text: PDF